PENANAMAN KARAKTER DISIPLIN PESERTA DIDIK SEKOLAH DASAR MELALUI PEMBIASAAN PAGI DALAM PERSPEKTIF BEHAVIORISME - Agustina Widianti; Dyah Sulistyaningsih; Widyastuti; Endang Fauziati; Bambang Sumardjoko (Pendas : Jurnal Ilmiah Pendidikan Dasar, 2025)
The lack of disciplinary character in learners is a challenge in education today. This study describes the process of instilling the character of students through daily habituation with a behaviorist approach, identifying the disciplinary character of students formed from routine activities and identifying the supporting factors for the success of the program. The research method used is descriptive qualitative method with data collection techniques through observation, interviews, and documentation. This research shows that morning habits such as ceremonies, gymnastics, rihlah, GELIS and SABAR are effective in improving student discipline. The success of this character building is supported by a conducive environment and the role of the teacher.